2020
DOI: 10.1158/1078-0432.ccr-19-0751
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Analyses of Response to Cyclin-Dependent Kinase 4/6 Inhibition and Endocrine Therapy in Women with Treatment-Naïve Metastatic Breast Cancer

Abstract: Purpose: Preclinical data identified the cyclin-dependent kinase 4/6 (CDK4/6) inhibitor palbociclib as synergistic with antiestrogens in inhibiting growth of hormone receptor-positive/human epidermal growth factor receptor 2-negative (HRþ/HER2À) human breast cancer models. This observation was validated clinically in the randomized, placebo-controlled, phase III PALOMA-2 study. Experimental Design: To determine markers of sensitivity and resistance to palbociclib plus letrozole, we performed comprehensive biom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(181 citation statements)
references
References 40 publications
10
156
0
Order By: Relevance
“…Previous findings have shown that patients with luminal subtype disease benefit from the combination of palbociclib plus letrozole, regardless of luminal A or luminal B subtype [27,31]. In patients with luminal A tumors, the median PFS was 30.4 months with palbociclib plus letrozole compared with 17.0 months with placebo plus letrozole (hazard ratio, 0.55; 95% CI 0.39-0.77; P = 0.000547) [27,31].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous findings have shown that patients with luminal subtype disease benefit from the combination of palbociclib plus letrozole, regardless of luminal A or luminal B subtype [27,31]. In patients with luminal A tumors, the median PFS was 30.4 months with palbociclib plus letrozole compared with 17.0 months with placebo plus letrozole (hazard ratio, 0.55; 95% CI 0.39-0.77; P = 0.000547) [27,31].…”
Section: Discussionmentioning
confidence: 91%
“…In PALOMA-3, women (n = 521) of any menopausal status with HR+/HER2− ABC whose disease had progressed after previous ET were randomized 2:1 to receive palbociclib (125 mg/day, 3/1 schedule) plus fulvestrant (500 mg on days 1 and 15 of cycle 1 and on day 1 of each subsequent cycle) or placebo plus fulvestrant [22]. Microarray data from the PALOMA-2 and PALOMA-3 studies were previously deposited in Gene Expression Omnibus (accession numbers GSE133394 and GSE128500, respectively); 568 baseline tumor tissues from either primary or metastatic biopsies were collected from patients in PALOMA-2 [27] and 462 tumor samples were collected, including 302 evaluable samples (53% archival primary samples and 47% metastatic biopsy samples), from PALOMA-3 [28].…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 3 more Smart Citations